iPhone and iPad Apps for Absolute Beginners - Lewis, Rory.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
The iPhone is the hottest gadget of our generation, and much of its success has been fueled by the App Store, Apple$1 (Bs online marketplace for iPhone applications. Over 1 billion apps have been downloaded in the 9 months the App Store has been open, ranging from the simplest games to the most complex business apps. Everyone has an idea for the next best-selling iPhone app$1 (Bpresumably that$1 (Bs why you$1 (Bre reading this now. And with the release of the iPad, this demand will just continue to grow. So how do you build an application for the iPhone and iPad? Don$1 (Bt you need to spend years learning complicated programming languages? What about Objective-C, Cocoa Touch, and the software development kit (SDK)? The answer is that you don$1 (Bt need to know any of those things. Anybody can start building simple applications for the iPhone and iPad, and this book will show you how. This book takes you to getting your first applications up and running using plain English and practical examples. It cuts through the fog of jargon and misinformation that surrounds iPhone and iPad application development, and gives you simple, step-by-step instructions to get you started. Teaches iPhone and iPad application development in language anyone can understand Provides simple, step-by-step examples that make learning easy Offers videos that enable you to follow along with the author$1 (Bit$1 (Bs like your own private classrooms
Before We Get Started -- Blast-Off! -- What$1 (Bs Next? -- An Introduction to the Code -- Buttons & Labels with Multiple Graphics -- Switch View with Multiple Graphics -- Dragging, Rotating, and Scaling -- Table Views, Navigation, and Arrays -- MapKit.s
Keywords: Computer science; Computer Science; Computer Science, general